A Comparative Study of the Educational Perspective of Charles Dickens and Houshang Moradi Kermani on Child Rights: A Case Study of Oliver Twist and the Children of the Carpet Weaving House - Saeid Rahimipour (Comparative Education Society of Iran ( CESIR), 2020)
The word "child" indicates a new concept and one of the achievements of the new civilization, while the concept of the rights of the child is more recent. For this reason, ignoring the rights of the child has become a global challenge recently that has had its impact on art and literature. Iranian society is no exception and child rights have been approached from different angles. Since the power of literary forms such as poetry, short stories, and novels on educating people and increasing their awareness of children's rights is great, the purpose of this article is the comparative analysis of two works by Charles Dickens and Iranian writer Houshang Moradi Kermani from the perspective of children's rights. The research method is analytical-inferential and the statistical population includes all the works of the two selected authors. The research sample is limited to two books, "Oliver Twist" by Charles Dickens and Bachehaye Qalibafkhaneh [The Children of the Carpet Weaving House] by Houshang Moradi Kermani, which have been purposefully selected. The method of data collection is documentary and the method of data analysis is thematic content analysis. The research findings indicate the commonalities of the two novels in revealing children's living conditions as the main and central theme of the stories. Another common denominator of the two novels is the concern of both authors about children's rights and the identification and explanation of their problems. While Dickens's goal is to reform society in favor of child rights, Kermani has tried to awaken the conscience of the people - without creating tension - by using language of humor against exploitation of children.